Biomass Juncus Derived Nitrogen-Doped Porous Carbon Materials for Supercapacitor and Oxygen Reduction Reaction - He, Guanghua; Yan, Genping; Song, Yonghai; Wang, Li (Frontiers in Chemistry, 2020)
Juncus is a worldwide perennial herb aquatic plant with high reproductive ability in warm regions. It has three-dimensional hierarchical porous triangular networks structures composited of tubular fibers. Here, juncus derived nitrogen-doped porous carbon (NDPC) was prepared by mixing juncus and ZnCl2 through one-step pyrolysis and activation, which was a low-cost, simple and environmentally friendly method. The NDPC had most of porous structures and high specific surface area, and was applied for supercapacitor and oxygen reduction reaction (ORR). The resulted NDPC-3-800 was used as electrode material of supercapacitor, it exhibited excellent specific capacitance of 290.5 F g-1 and 175 F g-1 in alkaline electrolyte at the current densities of 0.5 A g-1 and 50 A g-1, respectively, with a good cycle stability, the capacitance was maintained at 94.5% after 10000 cycles. NDPC-5-800 exhibited outstanding ORR catalytic activity and stability attributing to their high specific surface area and a lot of actives sites. Therefore, juncus is a renewable materials, it can derive various materials and apply to different fields widely.